The State’s Belligerent Reason for Existence: A Recurring Challenge to Pacem in Terris’s Theopolitical Ethical Vision - Pedregosa, Lawrence Santiago (Asian Horizons, 2023)
This theological ethical article reflects on the state’s belligerent reason for existence as a recurring challenge to Pacem in Terris’s vision. Rooted in natural law, Pope John XXIII’s social encyclical was groundbreaking for its universal appeal for world peace among states. Political theorists, however, see that the state is organized through wars and the monopolization of legitimate violence to enforce laws, secure order, and achieve peace. In this regard, Pacem in Terris responds to the state’s violent tendencies through the ethical principles of subsidiarity and universal human family. The practical limitations of smaller social bodies or the United Nations Organization as world authority nonetheless necessitate the continuing reliance on the state, despite its coercive practices, to realize the universal common good. Given this paradox, the article argues that Pope Francis’s ecclesial images of the Church as ‘mother to all’, ‘field hospital’, and ‘polyhedron’ offer insights to re-imagine the state as a social body based on the commons by unearthing its theopolitical ethical foundations in pursuance of peace.